CHALLENGES AND SOLUTIONS IN DEVELOPING BASIC COMPETENCIES OF SPEAKING SKILLS IN TOURISM AMONG 11 TH GRADE STUDENTS’ AT SMKN 1 GOWA - Salsa Aprilia J; Muh Nur Akbar Rasyid; Waode Surya Darmadali (Cakrawala Bahasa, 2026)
This study aims to analyze the challenges in developing basic competencies of speaking skills, to describe the influential factors faced by eleventh grade students majoring in Tourism Services Business at SMKN 1 Gowa, and to identify the learning strategies used to overcome those challenges. The research employed a descriptive qualitative method through observation and interviews with ten students to explore their experiences and strategies in learning English speaking. The findings reveal five main factors affecting students’ speaking performance: age, psychological, personality, sociocultural, and linguistic factors. Age factor relates to cognitive development,  psychological factors include fear of making mistakes and lack of motivation, personality factors involve individual traits such as shyness, sociocultural factors reflect environmental support and teaching methods, and linguistic factors cover limited vocabulary, grammar, and pronunciation issues. To address these challenges, students applied various learning strategies including metacognitive, cognitive, social, affective, and communicative approaches. These strategies help students plan, monitor, and evaluate their learning, expand vocabulary, and maintain interaction during communication. The study highlights that both internal and external factors influence students’ speaking skills, and that applying appropriate strategies enables them to improve their competence and confidence in English speaking.